Neonatal intensive care unit safety culture varies widely. Issue 2 (19th September 2011) - Profit, Jochen; Etchegaray, Jason; Petersen, Laura A; Sexton, J Bryan; Hysong, Sylvia J; Mei, Minghua; Thomas, Eric J
Abstract : Background: Variation in healthcare delivery and outcomes in neonatal intensive care units (NICUs) may be partly explained by differences in safety culture. Objective: To describe NICU care giver assessments of safety culture, explore variability within and between NICUs on safety culture domains, and test for association with care giver characteristics. Methods: NICU care givers in 12 hospitals were surveyed using the Safety Attitudes Questionnaire (SAQ), which has six scales: teamwork climate, safety climate, job satisfaction, stress recognition, perception of management and working conditions. Scale means, SDs and percent positives (percent agreement) were calculated for each NICU. Results: There was substantial variation in safety culture domains among NICUs. Composite mean score across the six domains ranged from 56.3 to 77.8 on a 100-point scale and NICUs in the top four NICUs were significantly different from the bottom four (p<0.001). Across the six domains, respondent assessments varied widely, but were least positive on perceptions of management (3%–80% positive; mean 33.3%) and stress recognition (18%–61% positive; mean 41.3%). Comparisons of SAQ scale scores between NICUs and a previously published adult ICU cohort generally revealed higher scores for NICUs. Composite scores for physicians were 8.2 (p=0.04) and 9.5 (p=0.02) points higher than for nurses and ancillary personnel. Conclusion: There is significant variation and scope for improvement in safety culture among these NICUs. The NICU variation was similar to variation in adult ICUs, but NICU scores were generally higher. Future studies should validate whether safety culture measured with the SAQ correlates with clinical and operational outcomes in NICUs.